2006
DOI: 10.1093/bja/ael008
|View full text |Cite
|
Sign up to set email alerts
|

Large volume N 2 O uptake alone does not explain the second gas effect of N 2 O on sevoflurane during constant inspired ventilation †

Abstract: We confirmed the existence of a SGE of N(2)O. Surprisingly, when using an Fa of 65% N(2)O, the magnitude of the SGE was the same with large or small VN(2)O. The classical model and the graphical representation of the SGE alone should not be used to explain the magnitude of the SGE. We speculate that changes in ventilation/perfusion inhomogeneity in the lungs during general anaesthesia result in a SGE at levels of VN(2)O previously considered by most to be too small to exert a SGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…This is consistent with most previous clinical and theoretical studies, including those of Peyton et al , who measured the second gas effect on arterial sevoflurane and oxygen partial pressures in anesthetized patients. 5,10 The augmentation to blood desflurane partial pressures at 20 to 30 min predicted by the model is in the order of 10 to 15% with moderate degrees of V̇/Q̇ scatter. This compares to a mean 12% increase in arterial sevoflurane partial pressures at this time point in ventilated patients measured by Peyton et al 10 The lesser augmentation in gas phase desflurane concentrations predicted here is also broadly consistent with the findings of Taheri and Eger, and those of Hendrickx et al for end-expired sevoflurane concentrations, in anesthetized patients.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This is consistent with most previous clinical and theoretical studies, including those of Peyton et al , who measured the second gas effect on arterial sevoflurane and oxygen partial pressures in anesthetized patients. 5,10 The augmentation to blood desflurane partial pressures at 20 to 30 min predicted by the model is in the order of 10 to 15% with moderate degrees of V̇/Q̇ scatter. This compares to a mean 12% increase in arterial sevoflurane partial pressures at this time point in ventilated patients measured by Peyton et al 10 The lesser augmentation in gas phase desflurane concentrations predicted here is also broadly consistent with the findings of Taheri and Eger, and those of Hendrickx et al for end-expired sevoflurane concentrations, in anesthetized patients.…”
Section: Discussionmentioning
confidence: 93%
“…This compares to a mean 12% increase in arterial sevoflurane partial pressures at this time point in ventilated patients measured by Peyton et al 10 The lesser augmentation in gas phase desflurane concentrations predicted here is also broadly consistent with the findings of Taheri and Eger, and those of Hendrickx et al for end-expired sevoflurane concentrations, in anesthetized patients. 4,5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NUMBER of studies [1][2][3] have shown that the rapid uptake of high concentrations of nitrous oxide at induction of inhalational anesthesia produces an increase in alveolar concentrations of oxygen and the accompanying volatile anesthetic agent. This process is known as the second gas effect.…”
mentioning
confidence: 99%